Potensi Penyalahgunaan Laporan Tahunan Yayasan dalam Tindak Pidana Pencucian Uang - Odilla, Iona Fahriyah; Aldevando, Desyla Putri; Rohmah, Amalia Sayyidatur (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2025)
Money laundering (TPPU) methods are becoming more sophisticated, including the misuse of foundations to channel illicit funds. A notable case occurred in 2022 involving alleged money laundering by the Aksi Cepat Tanggap Foundation, alongside PPATK’s discovery of suspicious transactions in 176 other philanthropic foundations. This research analyzes the role of foundations’ annual reports in such schemes and proposes regulatory improvements. Using a normative juridical method with statutory, conceptual, and comparative approaches, it draws from secondary literature. Foundations are legally required to submit annual reports detailing financial and operational activities. However, two major vulnerabilities are identified: the absence of standardized reporting guidelines and a lack of penalties for non-compliance. These gaps can facilitate money laundering through means such as anonymous donations, atypical transactions, inflated asset valuations, or fund misappropriation. To mitigate these risks, the study recommends developing clear and uniform reporting standards grounded in the principles of know your donor, know your beneficiary, and know your partner. Additionally, enforcement of administrative sanctions for failing to submit reports in line with regulations is crucial to strengthen oversight and transparency in the philanthropic sector.